Air Quality Characterisation and Modelling - Pires, José Carlos Magalhães; Gómez-Losada, Álvaro (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Air pollution is a mixture of particles and gases, which can reach unsafe concentrations for human health, the environment, vegetation, and materials. It has become one of the main sustainability issues and a concerning topic in atmospheric science. According to the World Health Organization (WHO), 90% of the world's population lives in highly polluted environments, and about 7 million premature deaths are caused yearly by outdoor and indoor air pollution. The combination of fast-growing populations, transport, fossil fuels, and biomass burning leads to pollution levels being especially high in some urban areas. Agriculture and natural phenomena are also important sources of pollution, underscoring the multi-faceted and transboundary nature of air pollution. The monitoring and understanding of the temporal and spatial behaviours of air pollutant concentrations are essential for both the implementation of air quality policies and the definition of effective measures to mitigate air pollution and its effects. Quantifying and monitoring exposure to air pollution in terms of public health is also a critical component in policy discussion. This reprint presents recent research activities concerning the characterization of air pollution and the applied modelling approaches.